Respuesta :

dilsai

Step-by-step explanation:

please mark me as brainlest

Ver imagen dilsai

Answer: x = -0.3

Step-by-step explanation:

Given expression

1 - 3 (9x + 3) = 3x + 1

Expand parentheses and apply the distributive property

1 - 27x - 9 = 3x + 1

Combine like terms

(1 - 9) - 27x = 3x + 1

-8 - 27x = 3x + 1

Subtract 3x on both sides

-8 - 27x - 3x = 3x + 1 - 3x

-8 - 30x = 1

Add 8 on both sides

-8 - 30x + 8 = 1 + 8

-30x = 9

Divide - 30 on both sides

(-30)x / (-30) = 9 / (-30)

(-30)x / (-30) = 3 / (-10)

[tex]\boxed{x=-0.3}[/tex]

Hope this helps!! :)

Please let me know if you have any questions

ACCESS MORE